(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The constitutional recognition of privacy in India has undergone a significant transformation, evolving from implicit acknowledgments within Article 21 to explicit validation through landmark judicial pronouncements. This review traces the constitutional journey of privacy in India, highlighting key judicial interpretations, legislative actions, and the interplay with societal norms. It examines the pivotal Supreme Court judgment in Justice K.S. Puttaswamy (Retd.) vs. Union of India (2017), which solidified privacy as a fundamental right, and explores subsequent legal and legislative developments. The review also addresses contemporary challenges posed by technological advancements, digital surveillance, and data protection, emphasizing the need for adaptive legal frameworks and robust enforcement mechanisms. By analyzing the dynamic interaction between the judiciary, legislature, and societal changes, this paper underscores the ongoing efforts and future directions necessary to uphold privacy as a cornerstone of personal liberty in India.